ANALISIS PENERAPAN PSAK NO. 45 TENTANG PELAPORAN KEUANGAN ENTITAS NIRLABA PADA PANTI ASUHAN AL-HUSNA BUKIT PAMULANG INDAH - Eka Kusuma Dewi; Muliyani Muliyani (LPPM Universitas Putera Batam, 2020)
This research is based on observations at the Al-Husna Orphanage at the Al-Husna Foundation in the Bukit Pamulang Indah Complex. Alpha fourteen. Pamulang Timur District. Tangerang Selatan Banten Province, foster children numbered thirty-five people with a total of twenty-six administrators. Foster children consisting of orphans do not have a father as head of the family and some are from poor families. Foster children in the range of education from elementary schools, junior high schools to high schools. The foster children are helped from school fees up to the day-to-day costs, but for their homes they are still cared for by their respective families. Every month they are gathered at the Masjid Al-Muhajirin Bukit Pamulang Indah Complex to monitor their educational development, their grades at school together with the provision of monthly compensation. For children who have achievements, the Al-Husna orphanage also gives prizes every semester with the aim of providing motivation to continue to perform and also to encourage his friends to achieve achievements as well. Once a year the foster children are also invited to travel with caregivers so they are happy and happy, such as to the top, to Bandung, and others. Meanwhile, the management consists of 26 residents from the area around the beautiful Pamulang hill complex in South Tangerang. These mothers come from different work backgrounds. There are housewives, employees, and who have their own businesses. Management is voluntary, without payment or salary. They really only aim to worship to help others. So far the Al Husna Orphanage in South Tangerang has received funds from permanent donors and donors. They have been keeping financial records simple. None of the administrators has a special ability to do bookkeeping. They simply record the income received from donors and expenses for their foster students. The purpose of this study is to look at financial reporting that has been carried out by the treasurer of the Al-Husna orphanage foundation. Furthermore, compile its financial reporting in accordance with PSAK standard no.45 regarding the financial reporting of non-profit organizations. Because the Orphanage is an organization that is not looking for profit, then PSAK 45 is in accordance with the nature of their organization. It is expected that by applying PSAK 45 for the preparation of their financial reports, financial accountability and transparency can be created so that they can be held accountable to foundations, donors and the public. This type of research uses descriptive qualitative research, with the steps of data collection, data processing or data analysis, preparation of reports and drawing conclusions.